Early and Late Com Plications of AstraZeneca Vaccine Booster Dose in Razi Teaching Hospital Staff in Ghaemshahr 1400 - Ahmad Alikhani; Hamideh Abbaspour Kasgari; Maysam Rezapour; Hajar Kakoei; Leyla Sepahi; Maedeh Moradpour Ivaki; Zohreh Alinasab baboli; Masoomeh Abdi Talarposhti (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: Due to the high spread of the coronavirus and the mode of transmission through touching contaminated surfaces and then touching the eyes, nose, or mouth, health workers have the highest risk of contamination, and vaccination of this workforce is necessary to reduce the risk, but this vaccination also resulted in high and common side effects such as local, systemic, early and late side effects. Therefore, the present study was conducted to investigate the early and late complications caused by the booster dose of the AstraZeneca vaccine in the personnel and medical staff of Razi Ghaemshahr Medical Training Center. Materials and methods: This descriptive cross-sectional study was conducted on all personnel and treatment staff of Razi Ghaemshahr Center in 1400. Participants were selected by convenience sampling method and a questionnaire related to the topical and specialized questions about booster vaccine side effects was used to collect the data. The data were analyzed using chi-square test and two-way logistic regression. Results: 302 health workers who received a booster dose of the AstraZeneca vaccine participated in this study. The participants had an average age of 34.89, 37.7% were men and 62.3% were women. The most common side effects of the vaccine include pain 64.2%, fatigue 58% and fever 54.6%. The participants were monitored for two months in terms of late complications, including heart attack, stroke, and pulmonary embolism after injecting a booster dose of AstraZeneca, and there were no reports of late complications. Conclusion: According to the results of this research, due to the possibility of more systemic side effects such as muscle pain, fatigue, cough, and fever after the injection, healthcare personnel should pay special attention to the early side effects of the vaccine.